The well-being of young leaders: demands and resources from a lifespan perspective - Irehill, Hanna; Lundmark, Robert; Tafvelin, Susanne (Frontiers in Psychology, 2023)
Building on the job demand resources (JD-R) model, we examined the experience of work environment and well-being among young leaders in a two-wave survey study of 1,033 leaders within the private sector in Sweden. Our results reveal that young leaders report higher levels of burnout and lower rates of vigor compared to older colleagues. Further, they appraise demand and resources differently, perceiving higher emotional demands and less organizational support, and they seem to struggle with the leader role, seeing it as unclear and conflicting. Our findings underline the necessity of viewing the leader role from a lifespan perspective as well as considering age-specific aspects in the JD-R model. In practice, we urge organizations to improve prerequisites for young leaders by providing support and role clarifications to prevent impaired well-being and improve retention. By bringing leadership and lifespan studies together, we aim for a better understanding of what specific prerequisites young leaders need to thrive in the leader role thus showing how age matters and bring the field of research forward.